IMPLEMENTASI STEM DI SEKOLAH DASAR DALAM MENGHADAPI TANTANGAN PEMBELAJARAN DAN PENDEKATAN PENDIDIKAN ABAD KE 21 - Pery Jayanto; Totok Victor Didik Saputro (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT The Science, Technology, Engineering, and Mathematics (STEM) approach has been widely recommended as an instructional strategy for addressing the demands of 21st-century skills, including critical thinking, creativity, collaboration, and communication. However, the implementation of STEM in elementary schools still faces various challenges related to teachers, curriculum, facilities, and students’ characteristics. This article aims to comprehensively examine the challenges of implementing STEM in elementary schools and their implications for the learning process. This  study employed a descriptive qualitative literature review. The research stages consisted of: (1) searching for articles from reputable national and international journals published within the last three years (2022–2024); (2) selecting articles based on predefined inclusion and exclusion criteria; (3) conducting content analysis to identify major themes related to STEM implementation challenges; and (4) synthesizing research findings to identify consistent patterns across studies. The results indicate that the main challenges include teachers’ limited understanding of STEM concepts and integration, lack of continuous professional development, insufficient learning facilities and media, and difficulties in aligning STEM with the existing curriculum. In addition, variations in elementary school students’ readiness levels also affect the effectiveness of STEM implementation. This article is expected to serve as a reference for educators and policymakers in developing more effective and sustainable strategies for strengthening STEM implementation in elementary schools. ABSTRAK Science, Technology, Engineering, and Mathematics (STEM) menjadi salah satu strategi pembelajaran yang direkomendasikan untuk menjawab tuntutan keterampilan abad ke-21, seperti berpikir kritis, kreativitas, kolaborasi, dan komunikasi. Namun, implementasi STEM di sekolah dasar (SD) masih menghadapi berbagai tantangan, baik dari aspek guru, kurikulum, sarana prasarana, maupun karakteristik siswa. Artikel ini bertujuan untuk mengkaji secara komprehensif tantangan implementasi STEM di sekolah dasar serta implikasinya terhadap proses pembelajaran. Penelitian ini menggunakan metode studi literatur dengan pendekatan deskriptif-kualitatif. Tahapan penelitian meliputi: (1) penelusuran artikel ilmiah dari jurnal internasional dan nasional bereputasi yang dipublikasikan dalam tiga tahun terakhir (2022–2024); (2) seleksi artikel berdasarkan kriteria inklusi dan eksklusi; (3) analisis isi (content analysis) untuk mengidentifikasi tema-tema utama terkait tantangan implementasi STEM; serta (4) sintesis hasil penelitian untuk memperoleh pola temuan yang konsisten. Hasil kajian menunjukkan bahwa tantangan utama implementasi STEM di sekolah dasar meliputi keterbatasan pemahaman guru tentang konsep dan integrasi STEM, minimnya pelatihan profesional berkelanjutan, keterbatasan fasilitas dan media pembelajaran, serta kesulitan dalam mengintegrasikan STEM dengan kurikulum yang berlaku. Selain itu, perbedaan kesiapan siswa sekolah dasar juga memengaruhi efektivitas penerapan STEM. Artikel ini diharapkan dapat menjadi rujukan bagi pendidik dan pemangku kebijakan dalam merumuskan strategi penguatan implementasi STEM yang lebih efektif dan berkelanjutan di sekolah dasar.